El papel de la atención primaria en la pandemia COVID-19: Una mirada hacia Europa - Ares-Blanco, Sara (Aten Primaria, 2021)
We describe the role of primary care (PC) in 12 European countries in relation to the COVID-19 pandemic. There is no official information at European level on the activity of PC. The findings were: All countries provided COVID-19 information through telephone lines and websites to their citizens. Contact tracing was mainly carried out by Public Health except for Ireland, Portugal and Spain. The epidemiological surveillance task has overlapped with the PC assistance. Active Infection Diagnostic Tests (AIDT) were performed in PC exclusively in Spain. The other countries performed them in external laboratories. Patients were followed-up in PC mostly by remote assessment. Health coverage for vulnerable populations and nursing homes has been regulated in all countries. There is a need for a strategic plan for PC in Europe that responds to the challenges posed.